Câu 6.52 trang 205 SBT Đại số 10 Nâng cao

Giải bài tập Câu 6.52 trang 205 SBT Đại số 10 Nâng cao

Quảng cáo

Đề bài

a) Chứng minh rằng nếu \(\cos \left( {\alpha  + \beta } \right) = 0\) thì \(\sin \left( {\alpha  + 2\beta } \right) = \sin \alpha \).

b) Chứng minh rằng nếu \(\sin \left( {2\alpha  + \beta } \right) = 3\sin \beta \) và \(\cos \alpha  \ne 0,\cos \left( {\alpha  + \beta } \right) \ne 0\) thì \(\tan \left( {\alpha  + \beta } \right) = 2\tan \alpha \)

Lời giải chi tiết

a) Nếu \(\cos \left( {\alpha  + \beta } \right) = 0\) thì

\(\begin{array}{l}\sin \left( {\alpha  + 2\beta } \right) = \sin \alpha \cos 2\beta  + \sin 2\beta \cos \alpha \\ = \sin \alpha \left( {1 - 2{{\sin }^2}\beta } \right) + 2\sin \beta \cos \beta \cos \alpha \\ = \sin \alpha  + 2\sin \beta \left( { - \sin \alpha \sin \beta  + \cos \alpha \cos \beta } \right)\\ = \sin \alpha  + 2\sin \beta \cos \left( {\alpha  + \beta } \right) = \sin \alpha \end{array}\)

Ta có

\(\begin{array}{l}\sin \left( {2\alpha  + \beta } \right) = 3\sin \beta \\ \Leftrightarrow 2\sin \alpha \cos \alpha \cos \beta  + \left( {2{{\cos }^2}\alpha  - 1} \right)\sin \beta  = 3\sin \beta \\ \Leftrightarrow \cos \alpha \sin \left( {\alpha  + \beta } \right) = 2\sin \beta \,\,\,\,\,\,\,\,\,\,\,\,\,\left( 1 \right)\end{array}\)

Mặt khác

\(\begin{array}{l}\sin \left( {2\alpha  + \beta } \right) = 2\sin \beta \\ \Leftrightarrow 2\sin \alpha \cos \alpha \cos \beta  + \left( {1 - 2{{\sin }^2}\alpha } \right)\sin \beta  = 3sin\beta \\ \Leftrightarrow \sin \alpha \cos \left( {\alpha  + \beta } \right) = \sin \beta \,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\left( 2 \right)\end{array}\)

Từ (1) và (2) suy ra \(\cot \alpha \tan \left( {\alpha  + \beta } \right) = 2.\) Do đó \(\tan \left( {\alpha  + \beta } \right) = 2\tan \alpha .\)   

Loigiaihay.com

Quảng cáo
list
close
Gửi bài